Feel, think, avoid: Testing a new model of advertising avoidance. Issue 4 (19th May 2021) - Kelly, Louise; Kerr, Gayle; Drennan, Judy; Fazal-E-Hasan, Syed Muhammad
ABSTRACT: Advertising avoidance is perhaps one of the greatest challenges facing marketers today. This study investigates the impact of emotions on advertising avoidance in social media. It tests five antecedents and two types of advertising avoidance, developing a new model of advertising avoidance. Data were collected via an online survey of 849 Facebook users and analyzed using structural equation modeling. The results of this study establish the important role of emotion in activating advertising avoidance. The study tests and validates two types of advertising avoidance: cognitive and behavioral (which includes mechanical). Further, the research also identifies five antecedents: attitude to social networking sites as an advertising medium, perceived clutter, negative word-of-mouth about advertising, and two new constructs of privacy concerns and control. These antecedents impact emotion and enact avoidance.